IMPLEMENTASI PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN BERBASIS KURIKULUM MERDEKA DI SEKOLAH DASAR - Sucahyo Mas'an Al Wahid; La Saharudin; Nayoh Nayoh (Universitas Borneo Tarakan, 2026)
The goal of national education is to develop abilities and shape the character and civilization of a dignified nation in order to educate the nation's life. Theoretical studies of the elements of physical education contribute to realizing the national goals of education. Because the program and objectives of physical education essentially shape human character to be good through the medium of movement. The researcher wanted to know the implementation of the Independent Curriculum that has been implemented in driving schools, especially elementary school level. The purpose of the study was to obtain information from driving teachers or driving schools regarding the supporting and inhibiting factors in the implementation of the independent curriculum. This research method uses a qualitative research methodology with a case study type. Data collection techniques were carried out through interviews, observation, and documentation. Interviews will use semi-structured interview guide instruments. The instrument used in observations is field notes. Documentation is carried out using checklist instruments and photos/videos of the implementation of the learning process. Data validity will use data source triangulation. Data analysis uses the Miles and Huberman model analysis. Informants consisted of driving teachers, principals, and elementary school students at Driving Schools. The benefits of the research results as a consideration for solutions to factors inhibiting the implementation of physical education and sports learning in elementary schools.